STRATEGI SURVIVAL DAN DETERMINAN PENDAPATAN UMKM DI AREA MAKAM BUNG KARNO DALAM ERA PANDEMI COVID-19 - Zainuri; Elbi Nugraha; Moh. Saleh; M. Fathorrazi (Jurnal Ilmiah Ekonomi Dan Bisnis, 2022)
This study aims to analyze the determinants of MSME income and formulate a survival strategy in the era of the COVID-19 pandemic. This research was conducted in the Bung Karno Tomb area, Blitar City, East java. This study uses primary data activities. The use of multiple linear regression aims to see the effect of capital, education and working hours on the income of the MSMEs. This study found that capital,education, and working hours had a positive and significant effet on income during the era of COVID-19. The strategy taken to survive during this COVID-19 was by changing employee entry schedules, cutting salaries, reducing types of merchandise that quickly expired and switching profession to handicrafts, t-shirts, batik and use social media such as Shopee and Facebook to boost their sales.